INTEGRATING LOCAL CULTURES IN TEACHING ENGLISH AS A FOREIGN LANGUAGE FOR CHARACTER BUILDING - Sukarno . (Jurnal Pendidikan Karakter, 2012)
Abstract: Teaching a language, including English, without contents is meaningless for it consists of merely symbols and grammatical rules. Considering that language is a means of communication, the contents can be the message to be transferred. The contents of teaching English as a foreign language will be more meaningful if they are related to students’ socio-economic cultural backgrounds. It does not mean that it ignores the ideas that teaching a language is also teaching its native speakers’ cultures because a language itself is a kind of cultural products. In teaching English as a foreign language, the cultures of its native speakers can be used as meaningful input texts to explore and elaborate local cultures consisting of moral values and local wisdoms meaningful for character building. To do so, teachers and lecturers teaching English are suggested that they not only discuss linguistic components, but also integrate local cultures consisting of moral values and wisdoms as the contents of their teaching skills. The steps are (1) rendering meaningful input texts related to cultures; (2) discussing contents; (3) exploring and elaborating local cultures especially for productive skills; (4) using appropriate English expressions; (5) discussing contents related to cultures consisting of moral values and wisdoms; and (6) emphasizing moral values and local wisdoms for character. Keywords: local cultures, teaching English as a foreign language, moral values, local wisdoms, character